2006
DOI: 10.1097/01.ta.0000240113.13552.96
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for the Patient to ???Sober Up???: Effect of Alcohol Intoxication on Glasgow Coma Scale Score of Brain Injured Patients

Abstract: Alcohol intoxication does not result in clinically significant changes in GCS score for patients with blunt TBI. Hence, alterations in GCS score after TBI should not be attributed to alcohol intoxication, as doing so might result in inappropriate delays in monitoring and therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 20 publications
3
54
1
4
Order By: Relevance
“…13 In contrast to this, 2 other studies failed to demonstrate a clinically significant effect of alcohol in the vast majority of TBI patients. 7,17 However, subgroup analyses in these 2 studies showed some effect in the more injured patients. Sperry et al found a clinically significant effect (defined as > 1 point GCS score difference) of alcohol among intoxicated patients (BAC > 80 mg/dl) in the most injured patients: those with head AIS scores of 5.…”
Section: Influence Of Alcohol and Effect On Gcs Scorementioning
confidence: 99%
See 4 more Smart Citations
“…13 In contrast to this, 2 other studies failed to demonstrate a clinically significant effect of alcohol in the vast majority of TBI patients. 7,17 However, subgroup analyses in these 2 studies showed some effect in the more injured patients. Sperry et al found a clinically significant effect (defined as > 1 point GCS score difference) of alcohol among intoxicated patients (BAC > 80 mg/dl) in the most injured patients: those with head AIS scores of 5.…”
Section: Influence Of Alcohol and Effect On Gcs Scorementioning
confidence: 99%
“…7 Several other studies have, however, used a single cutoff for BAC to classify patients into 2 groups. 13,17,21 Thus, they fail to identify any dose-dependent relationships between BAC and GCS scores, and the effects from very high BAC may be missed. Large individual differences in alcohol tolerance also militate against the use of a single cutoff value.…”
Section: Effect Of Alcohol In Patients With Moderate and Severe Tbimentioning
confidence: 99%
See 3 more Smart Citations